Egy bácskai ügyvéd utazásai a "Keleti ég alatt" - Gyuris István Viktor; Móra Kárpát-medencei Interdiszciplináris Szakkollégiumi Konferencia (3.) (2019) (Szeged) (2021)
Károly Vértesi (1843–1917) was a middle-class citizen of the Austro-Hungarian Monarchy, whose worldview was grounded in Western modernity. He became a well-kown literary figure after publishing his reports in press about his eastern travel (Egypt, Palestine, Constantinople) in 1887. His trip reports reflect more so the modern European self-image, than the witnessed realities. Vértesi framed the “East” as both a mysterious land full of wonder, but also a place of extreme darkness and backwardness. As a devotee of the industrial revolution Vértesi often entertained the thought of a civilizing mission modernizing the East. His travelogue is a detailed account of many topics from the late 19th century: the differences of the modern and the traditional world, orientalist framings of the East, the usage of the ancient Egyptian heritage.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Nyelvek és irodalom